Question

# If 1,z1,z2,...,zn−1 are the roots of zn−1=0, then 13−z1+13−z2+13−z3+...+13−zn−1 is equal to

A
n1r=1r3r1nr=13r1
Right on! Give the BNAT exam to get a 100% scholarship for BYJUS courses
B
nr=1r3r1nr=13r1
No worries! We‘ve got your back. Try BYJU‘S free classes today!
C
n3n13n112
Right on! Give the BNAT exam to get a 100% scholarship for BYJUS courses
D
n3n3n112
No worries! We‘ve got your back. Try BYJU‘S free classes today!
Open in App
Solution

## The correct options are A n−1∑r=1r⋅3r−1n∑r=13r−1 C n⋅3n−13n−1−12 1,z1,z2,...,zn−1 are the roots of zn−1=0 ⇒(z−1)(z−z1)(z−z2)...(z−zn−1)=0 ⇒1+z+z2+...+zn−1=0 Replace 13−z=y⇒z=3y−1y 1+3y−1y+(3y−1y)2+...+(3y−1y)n−1=0 Multiply by yn−1 ⇒yn−1+yn−2(3y−1)+yn−3(3y−1)2+...+(3y−1)n−1=0 ⇒yn−1(1+3+32+...+3n−1)− yn−2(1+2⋅3+3⋅32+4⋅33+...+(n−1)3n−2) +...+(−1)n−1=0 We know that, sum of roots =−ba ∴13−z1+13−z2+13−z3+...+13−zn−1=1+2⋅3+3⋅32+4⋅33+...+(n−1)3n−21+3+32+...+3n−1 =n−1∑r=1r⋅3r−1n∑r=13r−1 Let S=n−1∑r=1r⋅3r−1 S=1+2⋅3+3⋅32+4⋅33+...+(n−1)3n−2 3S= 3+2⋅32+3⋅33+...+(n−2)3n−2+(n−1)3n−1 Subtracting above equations, we get −2S=3n−1−12−(n−1)3n−1 ⇒S=n⋅3n−12−3n−14 S′=n∑r=13r−1=3n−12 Required Answer= =n⋅3n−13n−1−12

Suggest Corrections
0
Join BYJU'S Learning Program
Related Videos
What Is a Good Fuel?
MATHEMATICS
Watch in App
Join BYJU'S Learning Program